Antimicrobial resistance of selected invasive bacteria in a tertiary care center: results of a prospective surveillance study - Djuric, Olivera; Jovanovic, Snezana; Stosovic, Branka; Tosic, Tanja; Jovanovic, Milica; Markovic-Denic, Ljiljana (The Journal of Infection in Developing Countries, 2016)
Introduction: We aimed to report the distribution and resistance patterns of eight invasive clinically relevant bacteria surveyed in the Clinical Center of Serbia (CCS) in Belgrade. Methodology: A total of 477 clinical blood stream isolates of Staphylococcus aureus, Streptococcus pneumoniae, Enterococcus faecium, Enterococcus faecalis, Klebsiella pneumoniae, Escherichia coli, Pseudomonas aeruginosa, and Acinetobacter spp. were collected in the period from January to December 2013. Antimicrobial susceptibility testing was performed using standard methods and interpreted using the Clinical and Laboratory Standards Institute (CLSI) breakpoint criteria. Results: Acinetobacter spp. was the most prevalent bacteria encountered (37%), followed by K. pneumoniae (25.7%). Multidrug resistance was observed in 92.5% of all isolates. Out of 177 strains of Acinetobacter spp., 97.7% were resistant to fluoroquinolones and carbapenems. Resistance to aminoglycosides, fluoroquinolones, and third-generation cephalosporins was 97.1%, 95.4%, and 95.8% among K. pneumoniae and 21.4%, 21.7%, and 31% among E. coli isolates, respectively. In total, 65.1% of K. pneumoniae and 12.1% of E. coli isolates were determined to be extended-spectrum beta-lactamase (ESBL) positive. High-level aminoglycoside resistance of E. faecalis was 71.4%, and glycopeptide resistance of E. faecium was 95%. Out of 66 strains of S. aureus, 63.4% were methicillin resistant. Conclusions: The majority of bloodstream isolates of clinically relevant bacteria in CCS were multidrug resistant. The biggest concerns are carbapenem-resistant Acinetobacter spp., K. pneumoniae, and P. aeruginosa; third-generation cephalosporin-resistant E. coli; vancomycin-resistant E. faecium; and methicillin-resistant S. aureus. Stricter measures of infection control and antibiotic use are needed.